Guru Profesional dalam Mengembangkan Media Pembelajaran IPS di SD Negeri 3 Karangkemojing - Rini, Ambar; Ningsih, Tutuk (YASIN, 2025)
This research is motivated by the important role of teachers' professional competence in improving the quality of learning, especially in the development of innovative and contextual learning media. This study aims to describe how teachers at SD Negeri 3 Karangkemojing develop social studies learning media to increase students' understanding and interest in learning. This study uses qualitative descriptive method with data collection techniques through in-depth interviews, class observations, and documentation studies, which are analyzed thematically. The results show that even though teachers face limitations in terms of technology and training, they are still able to develop learning media through collaborative strategies, the use of local resources, and the use of simple technology. The conclusion of this study is that the teacher's competence and creativity are the main factors in creating learning media that is interesting, relevant, and contributes to the formation of students' character in accordance with the curriculum. This research is expected to provide implications for elementary school teachers in developing aspects of their professional competence.